2014
DOI: 10.1186/1471-2164-15-758
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association analysis for porcine serum lipid traits reveals the existence of age-specific genetic determinants

Abstract: BackgroundThe genetic determinism of blood lipid concentrations, the main risk factor for atherosclerosis, is practically unknown in species other than human and mouse. Even in model organisms, little is known about how the genetic determinants of lipid traits are modulated by age-specific factors. To gain new insights into this issue, we have carried out a genome-wide association study (GWAS) for cholesterol (CHOL), triglyceride (TRIG) and low (LDL) and high (HDL) density lipoprotein concentrations measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 50 publications
3
27
1
Order By: Relevance
“…A). QTL and GWAS techniques have also identified seemingly modular age‐specific allelic effects in a wide range of organisms . These studies have all reported that the polymorphisms contributing to trait variation are different at different ages.…”
Section: Genetic Modularity Of Life Histories: the Case For Evolutionmentioning
confidence: 99%
“…A). QTL and GWAS techniques have also identified seemingly modular age‐specific allelic effects in a wide range of organisms . These studies have all reported that the polymorphisms contributing to trait variation are different at different ages.…”
Section: Genetic Modularity Of Life Histories: the Case For Evolutionmentioning
confidence: 99%
“…GEMMA was also employed to estimate the proportion of variance in phenotypes explained by SNP genotypes (i.e. “chip heritability”) using the following formula:hSNP2=σG2normalσG2+normalσE2where σG2 is the variance due to SNPs and σE2 is the variance of residuals (Manunza et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Quality genotyping analyses were carried out with the GenomeStudio software (Illumina), as previously reported14. We removed SNPs (a) mapping to the X chromosome, (b) with a rate of missing genotypes higher than 5%, (c) that did not conform Hardy-Weinberg expectations (threshold set at a P -value ≤ 0.001), (d) that had a minor allele frequency below 0.05, (e) that had a GenCall score < 0.15, (f) that had a call rate < 95% or (g) that could not be mapped to the pig genome ( Sus scrofa 10.2 assembly).…”
Section: Methodsmentioning
confidence: 99%